Mixed convection heat transfer of a nanofluid in a lid-driven enclosure with two adherent porous blocks - Bondarenko, Darya S.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Springer, 2019)
Convective flow and heat transfer in an alumina/water nanofluid enclosure having two centered adherent porous blocks under the effect of moving upper wall have been analyzed numerically. The control parameters are the Richardson number (0.01Ri10), dimensionless porous blocks size (0.10.4) and concentration of solid nanoparticles (0 phi 0.04). The calculated results have shown the growth of the heat transfer rate with nanoparticles concentration for forced convection regime (Ri<1) and the heat transfer rate reduction for mixed and natural convection regimes (Ri 1) for the medium size of the porous blocks, while the average Nusselt number increases with the Richardson number for high size of porous blocks.
Keywords: Mixed convection; Square enclosure; Moving upper wall; Porous blocks; Nanoliquid; Numerical results